Venous thromboembolism following 672, 495 primary total shoulder and elbow replacements: Meta-analyses of incidence, temporal trends and potential risk factors. Issue 189 (May 2020) - Kunutsor, Setor K.; Barrett, Matthew C.; Whitehouse, Michael R.; Blom, Ashley W.
Abstract: Background: There is wide variability in reported venous thromboembolism (VTE) incidence following total shoulder replacement (TSR) or total elbow replacement (TER). It is uncertain which risk factors influence the risk of VTE following TSR or TER. We conducted a PRISMA compliant meta-analysis to evaluate the incidence, temporal trends and potential risk factors for VTE following primary TSR and TER. Methods: MEDLINE, Embase, Web of Science, and Cochrane Library were searched to September 2019 for longitudinal studies reporting VTE outcomes after TSR or TER. Incidence and relative risks (RR) (95% confidence intervals) were estimated. Results: We identified 43 articles with data on 672, 495 TSRs and TERs (668, 699 TSRs and 3796 TERs). The overall pooled 3-month VTE incidence following TSR was 0.85% (0.39–1.46). For TER, the 3-month incidence of VTE was 0.23% (0.08–0.44). Older age, body mass index (BMI) ≥25 kg/m 2, and alcohol abuse were each associated with increased VTE risk following TSR. Comorbidities associated with increased VTE risk following TSR were chronic pulmonary disease, previous VTE, heart failure, anaemia, coagulopathy, arrhythmia, epilepsy, urinary tract infection, sleep apnoea, and fluid & electrolyte imbalance. Anatomic and outpatient TSR were each associated with decreased VTE risk. Conclusions: The average 3-month incidence of VTE following TSR or TER is <1%. High risk groups such as older patients, those with a previous VTE history and those undergoing reverse or inpatient TSR may need close monitoring. Modifiable factors such as high BMI, alcohol abuse, and comorbidities could be identified and addressed prior to surgery. Systematic review registration: PROSPERO 2019: CRD42019134096. Highlights: 3-month VTE incidence following TSR is 0.85% 3-month VTE incidence following TER is 0.23% Older age, high BMI and alcohol abuse increase VTE risk following TSR Several comorbidities including previous VTE increased VTE risk Anatomic and outpatient TSR each decreased VTE risk.